Interactions of APE1 with a redox inhibitor: Evidence for an alternate conformation of the enzyme - Su, Dian (2010)
Apurinic/apyrimidinic endonuclease (APE1) is an essential base excision repair protein that also functions as a reduction/oxidation (redox) factor in mammals. Through a thiol-based mechanism, APE1 reduces a number of important transcription factors including AP-1, p53, NF-κB, and HIF-1α. What is known about the mechanism to date is that the buried Cys residues 65 and 93 are critical for APE1’s redox activity. To further detail the redox mechanism, we developed a chemical footprinting/mass spectrometric assay using N-ethylmaleimide (NEM), an irreversible Cys modifier, to characterize the interaction of the redox inhibitor, E3330, with APE1. When incubated with E3330, two NEM-modified products were observed, one with 2 and a second with 7 added NEMs; this latter product corresponds to a fully modified APE1. In a similar control reaction without E3330, only the +2NEM product was observed in which the two solvent accessible Cys residues, C99 and C138, were modified by NEM. Through hydrogen-deuterium amide exchange with analysis by mass spectrometry, we found that the +7NEM modified species incorporates approximately 40 more deuterium atoms than the native protein, which exchanges nearly identically as the +2NEM product, suggesting that APE1 can be trapped in a partially unfolded state. E3330 was also found to increase disulfide bond formation involving redox critical Cys residues in APE1 as assessed by LC-MS/MS, suggesting a basis for its inhibitory effects on APE1’s redox activity. Collectively, our results suggest that APE1 adopts a partially unfolded state, which we propose is the redox active form of the enzyme.